Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jat.3516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on kitl pre‐mRNA alternative splicing in murine ovarian granulosa cells and its associated regulation by miRNAs

Abstract: In this study, we established an in vitro exposure model of murine ovarian granulosa cells to observe the effect of Cd on alternative splicing of the kitl pre-mRNA and subsequently to explore the role of kitl gene expression regulation-related miRNAs through miRNA prediction, miRNA chip, bioinformatics and real-time quantitative polymerase chain reaction analyses. Our results showed that the kitl1/kitl2 mRNA ratio was significantly different (P < 0.05) at different dosages and times. The miRNA chip analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Ovaries are one organ known to be susceptible to Cd accumulation and have a greater potential risk for toxicity either before or during pregnancy [55]. In ovarian granulosa cells, a 4-h exposure to Cd resulted in altered expression of five miRNAs involved in the kit ligand (kitl ) pre-mRNA alternative splicing [56]. Cd has been identified as a possible causative agent for preeclampsia, in which the ability of Cd to bioaccumulate increases its potential toxicity.…”
Section: Cadmium-associated Changes In Mirna Expressionmentioning
confidence: 99%
“…Ovaries are one organ known to be susceptible to Cd accumulation and have a greater potential risk for toxicity either before or during pregnancy [55]. In ovarian granulosa cells, a 4-h exposure to Cd resulted in altered expression of five miRNAs involved in the kit ligand (kitl ) pre-mRNA alternative splicing [56]. Cd has been identified as a possible causative agent for preeclampsia, in which the ability of Cd to bioaccumulate increases its potential toxicity.…”
Section: Cadmium-associated Changes In Mirna Expressionmentioning
confidence: 99%
“…MiR-107 targets 21 DEGs, including five steroidogenic genes: HMGCS1, FDFT1, CYP51A1, SQLE, and EBP. miRNA-107 expression in murine ovarian GCs exposed to cadmium was significantly different from expression in the control group, and miRNA-107 can regulate kit ligand (kitl) expression (Wang et al, 2018). Kitl plays an important role in the recruitment of primitive follicles (Parrott & Skinner 1999), the proliferation and differentiation of GCs, the recruitment of theca cells, and early steroid hormone synthesis (Flanagan et al, 1991).…”
Section: Hydroxyprogesterone Acts As An Intermediate During the Convementioning
confidence: 99%
“…It is also possible that external and environmental factors may be linked to AS that can affect the Hippo pathway. A recent paper from the Zhang group [ 84 ] shows that the toxic metal cadmium, which can enter the body through contaminated water, air and food, and can readily accumulate in the body and particularly the ovaries, can affect kit ligand ( KITL ) pre-mRNA AS of exon 6 changing the ratio of kitl1/kitl2 mRNA. Treatment of murine ovarian cells with cadmium was shown to affect the expression of 29 microRNAs (miRNAs) associated with the KITL gene [ 84 ].…”
Section: Examples Of Alternative Splicing In the Hippo Pathwaymentioning
confidence: 99%
“…A recent paper from the Zhang group [ 84 ] shows that the toxic metal cadmium, which can enter the body through contaminated water, air and food, and can readily accumulate in the body and particularly the ovaries, can affect kit ligand ( KITL ) pre-mRNA AS of exon 6 changing the ratio of kitl1/kitl2 mRNA. Treatment of murine ovarian cells with cadmium was shown to affect the expression of 29 microRNAs (miRNAs) associated with the KITL gene [ 84 ]. Gene ontology analysis showed that the target genes of these 29 miRNAs were enriched in biological processes such as cellular metabolism, signal transduction, cell cycle and proliferation, differentiation and migration.…”
Section: Examples Of Alternative Splicing In the Hippo Pathwaymentioning
confidence: 99%
See 1 more Smart Citation